DEVELOPMENT OF DIGITAL ECONOMY AND ELECTRONIC GOVERNMENT. (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
In accordance with the strategy "Digital Uzbekistan - 2030" in our country, digitalization of economic sectors and regions, introduction of state information systems and electronic services, as well as public education, public services, judiciary, finance and complex measures are being implemented in the banking system.